In Silico Study of Moringa Leaf (Moringa oleifera L.) Compounds as an Antiproliferative in Hepatocellular Carcinoma against TGF-β Receptor - Arnees Angzora; Athena Lilavya Putri; Johanna Felicia Susanto; Kathlia Putri Alyanisa; Debian Mydea Erliputeri; Nawadhir Fauzan; Shela Salsabila; Muchtaridi Muchtaridi (ALCHEMY Jurnal Penelitian Kimia, 2026)
Liver cancer is a condition in which liver cells grow uncontrollably. Liver cancer, also known as hepatoma, occurs when cells proliferate and acquire malignant properties. Liver cancer is among the types of cancer with a high contribution to global mortality rates each year. This study aims to predict and identify the activity of compounds isolated from Moringa leaves (Moringa oleifera L.) against liver cancer by targeting the TGF-β receptor using molecular docking. The research was conducted using software tools including LigandScout, ADMETlab 2.0, BIOVIA Discovery Studio Visualizer, and AutoDock Tools. The results showed that ten out of eleven test compounds from Moringa oleifera L. leaves met Lipinski's Rule of Five, indicating their potential as good oral drug candidates. Pharmacophore screening yielded an AUC100 value of 0.94 with three hit compounds: rutin, kaempferol, and isorhamnetin. In the molecular docking stage, the compound with the lowest binding energy was Isorhamnetin, with a binding energy of -8.18 kcal/mol against the TGF-β receptor, and it also demonstrated a favorable ADMET profile.